Direct and Indirect Effects of Investment Tax Incentives - Lerche, Adrian (American Economic Review, 2025)
This paper estimates the direct effects and indirect spillover effects of investment tax credits on firms. Exploiting a differential tax credit rate change by firm size in the German manufacturing sector, I find that lowering a firm's investment cost by 7.6 percent increases its capital stock by 17.7 percent and employment by 12.0 percent. Positive local spillovers generate one additional manufacturing job for each directly created job, are strongest between firms in industries connected through input-output linkages, and arise within distances of five kilometers. Firms dependent on local consumer demand also increase employment, while within-industry spillovers generate small negative effects. (JEL D22, H25, H32, J23, L25, L60, R11)